PENGARUH PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TOKO ANDESTI JAYA DI BOJONG SARI KOTA DEPOK - Abrar, Fauzan; Mustakim, Masran (Journal of Research and Publication Innovation, 2024)
The aim of this study is to determine the effect of Price Perception and Service Quality on Customer Satisfaction at Andesti Jaya Store in Bojong Sari, Depok City, both partially and simultaneously. The method used is quantitative. The sampling technique used is probability/random sampling, employing a random selection process that gives each member of the population an equal chance to be selected as a sample, resulting in a sample size of 100 respondents. The results show that Price Perception (X1) and Service Quality (X2) have a significant effect on Customer Satisfaction, with the regression equation Y = 11.197 + 0.302X1 + 0.439X2. The correlation coefficient or the level of influence between the independent variables and the dependent variable is 0.798, indicating a strong relationship. The coefficient of determination is 0.503, which means that the variables Price Perception and Service Quality affect the variable Customer Satisfaction by 50.3%, while the remaining 49.7% is influenced by other factors not studied. The hypothesis test shows that the calculated F value is greater than the F table value (49.061 > 3.090), and this is also supported by a ρ value < Sig.0.05 (0.000 < 0.05). Therefore, H0 is rejected and H3 is accepted, indicating that there is a significant simultaneous effect of Price Perception and Service Quality on Customer Satisfaction at Andesti Jaya Store in Bojong Sari, Depok City.